Catheter treatment of junctional reciprocating tachycardia - P. A. Almiz; A. S. Stychynsky; N. V. Plyska; A. V. Pokanevitch; A. V. Kovalchuk; S. L. Tkachuk (Ukrainian Journal of Cardiovascular Surgery, 2016)
The analysis of basic electrophysiologic features of junctional reciprocating tachycardia and results of catheter ablation for this arrhythmia were held in this work.